Menimbang Teori Kronologi Al-Qur’an Sir William Muir dan Hubbert Grimme - Ali Fitriana Rahmat (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
This article is a review of the chronological theory of the Qur'an offered by two orientalists who lived in the 19th century, namely Sir William Muir (1819-1905 AD) and Hubbert Grimme (1864-1942 AD). The periodization of the Koran which was carried out by both of them rests on historical and theological approaches. This study used a descriptive method with primary data sources in the form of two works of the two orientalists, namely The Coran; Its Composition and Theacing; and the Testimony it Bears to the Holy Scriptures by Muir and also a book called Mohammed; Einleitung in den Koran System der newspapersischen Theologie. The results of this study conclude that first, the Muir version of the Makkiyah surah is 93 chapters, while the Madaniyah versions are 21 chapters. Second, the Grimme version of the Makkiyah surah has 92 chapters, while the Madaniyah version has 22 chapters.